Herbs-Partitioned Moxibustion Combined with Acupuncture Inhibits TGF-β1-Smad-Snail-Induced Intestinal Epithelial Mesenchymal Transition in Crohn's Disease Model Rats. (30th May 2019) - Shi, Yin; Li, Tao; Zhou, Jing; Li, Yuwei; Chen, Liu; Shang, Haixia; Guo, Yajing; Sun, Yi; Zhao, Jimeng; Bao, Chunhui; Wu, Huangan
Abstract : Crohn's disease may cause excessive damage and repair in the intestinal epithelium due to its chronic relapsing intestinal inflammation. These factors may initiate the TGF- β 1-Smad pathway to activate the transcription factor of Snail, and the Snail-mediated pathway promotes the transformation of intestinal epithelial cells to mesenchymal cells, leading to intestinal fibrosis. Acupuncture and moxibustion have been demonstrated to prevent intestinal fibrosis in Crohn's disease. However, it is not clear whether acupuncture and moxibustion can inhibit intestinal epithelial mesenchymal transformation in Crohn's disease by affecting the TGF- β 1-Smad-Snail pathway. This study indicated that abnormal increased expressions of TGF β 1, T β R2, Smad3, and Snail were significantly downregulated by herbs-partitioned moxibustion at Tianshu (ST25) and Qihai (RN6) and acupuncture at Zusanli (ST36) and Shangjuxu (ST37). In addition, protein and mRNA levels of E-cadherin, the epithelial cell marker, were significantly increased. Protein and mRNA levels of fibronectin, the mesenchymal cell marker, were decreased in the intestinal tissue. Moreover, the number of mesenchymal cells in the intestinal mucosa can be reversely transformed to intestinal epithelial cells. Therefore, herbs-partitioned moxibustion combined with acupuncture can prevent intestinal epithelial mesenchymal transition by inhibiting abnormal expression of TGF β 1, T β R2, Smad3, and Snail in the TGF- β 1-Smad-Snail pathway in Crohn's disease.